Wearable PIFA antenna implemented on jean substrate for wireless body area network. Issue 11 (13th August 2017) - Gil, I.; Fernández-García, R.
Abstract: A novel wearable PIFA antenna jeans substrate topology have been designed, simulated and tested. This paper investigates the impact of introducing an additional substrate in order to improve the antenna performance, shielding effect in terms of SAR and degree of wearability, in comparison with the standard topology. The proposed embroidered PIFA involves a ground plane sandwiched by two jeans substrates and requires a 50 × 16 mm area. It operates at 2.45 GHz presenting a 1.98 dBi gain with a 29.1% efficiency in contact with the human body. On-voxel analysis reveals that SAR standards are satisfied for occupational sector in any case and for public exposure at 1 cm from the body.